The realization of the antimonopoly and competition policy in Ukraine - Верещагіна, О. С. (Theory and practice of jurisprudence, 2016)
Тhis article investigates the question concerning stage of the realization of the antimonopoly and competition policy, with grounding of this term usage, check up the content of the stage, its subjects, who are authorized to realize this policy. The results of investigations allow us to formulate our own definition of the stage of the realization of the antimonopoly and competition policy